2001
DOI: 10.1515/epoly.2001.1.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Sm based initiators for the ring-opening polymerization of L-lactide

Abstract: Ring-opening polymerizations of L-lactide were carried out in the presence of Sm(II) (SmI2/Sm) and the Sm(III) complex [Sm(m-Cl){N(SiMe3)2}2(THF)]2 (Me: CH3, THF: tetrahydrofuran). The polymerizations were performed using different mole ratios of monomer to initiator and for different time intervals. The complexes were found to be active polymerization catalysts and led to the synthesis of semicrystalline, optically active poly(L-lactide) retaining about 95.5% of the optical activity. This shows that - with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 0 publications
2
18
0
2
Order By: Relevance
“…Indeed, the displacement of THF by ε‐CL is to be expected based on previous studies highlighting the stronger coordinating strength of the lactone over the ether 3. 36, 37, 50 Although 1 b could not be isolated since it rapidly evolved towards the formation of 2 (vide infra), it could be characterized in situ by its 1 H NMR (Figure 2) and 11 B{ 1 H} NMR spectra. The 11 B NMR chemical shift of 1 b is similar to that of 1 a .…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, the displacement of THF by ε‐CL is to be expected based on previous studies highlighting the stronger coordinating strength of the lactone over the ether 3. 36, 37, 50 Although 1 b could not be isolated since it rapidly evolved towards the formation of 2 (vide infra), it could be characterized in situ by its 1 H NMR (Figure 2) and 11 B{ 1 H} NMR spectra. The 11 B NMR chemical shift of 1 b is similar to that of 1 a .…”
Section: Resultsmentioning
confidence: 75%
“…Polymerization by single‐site trivalent rare‐earth initiators, supported or unsupported, has been essentially developed with olefinic monomers 18. 19 With lactones, monohapto mono‐alkoxide,2024 ‐amide,2429 ‐hydride,23 ‐alkyl,23, 30–35 ‐halide,24, 36, 37 and ‐phosphorane iminato38 organo‐rare‐earth derivatives have been used as effective initiators. These incorporated spectator ligands as varied as halide,20, 37, 38 alkyl,22 cyclopentadienyl,23, 26, 30, 31, 33–35 bridged fluorenyl cyclopentadienyl,28 phospholyl,20 cyclooctatetraenyl,25, 37 pyrrolyl,27 phenolato,29 acetate,21 amide,36, 37 amidinate,24, 25 guanidinate,32 and phosphorane iminato,26, 38 as well as mono‐ or dinuclear and even “ate”22, 24 complexes.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is however challenging in the face of other processes that can produce He + ionising photons. Additionally, the short life-time of ∼ 1Myr of pop-III systems and resulting ISM/IGM pollution by pairinstability supernovae (Heger & Woosley 2002), uncertainties in photometric calibrations, presence of active galactic nuclei (AGN), pristine cold mode gas accretion to galaxies, limited understanding of high-redshift stellar populations and ISM contribute further to the complexity of detecting and identifying pop-III host systems (Fardal et al 2001;Yang et al 2006;Sobral et al 2015;Agarwal et al 2016;Bowler et al 2017;Matthee et al 2017;Shibuya et al 2017;Sobral et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of catalysts could be used for this synthesis (13)(14)(15)(16) and lanthanide-based catalytic systems proved to be highly active in ring-opening polymerization (17)(18)(19)(20)(21). Stuerga et al (22) has reported a new synthetic pathway of PCL using microwave irradiation without any solvent, using nontoxic, biologically acceptable lanthanide halides as initiators instead of using expensive lanthanide alkoxides.…”
Section: Figurementioning
confidence: 99%